Prediction of a clinically effective dose of THY1773, a novel V1Breceptor antagonist, based on preclinical data. (3rd April 2021) - Inatani, Shoko; Mizuno‐Yasuhira, Akiko; Kamiya, Makoto; Nishino, Izumi; Sabia, Helene D.; Endo, Hiromi
Abstract: THY1773 is a novel arginine vasopressin 1B (V1B ) receptor antagonist that is under development as an oral drug for the treatment of major depressive disorder (MDD). Here we report our strategy to predict a clinically effective dose of THY1773 for MDD in the preclinical stage, and discuss the important insights gained by retrospective analysis of prediction accuracy. To predict human pharmacokinetic (PK) parameters, several extrapolation methods from animal or in vitro data to humans were investigated. The fu correction intercept method and two‐species‐based allometry were used to extrapolate clearance from rats and dogs to humans. The physiologically based pharmacokinetics (PBPK)/receptor occupancy (RO) model was developed by linking free plasma concentration with pituitary V1B RO by the Emax model. As a result, the predicted clinically effective dose of THY1773 associated with 50% V1B RO was low enough (10 mg/day, or at maximum 110 mg/day) to warrant entering phase 1 clinical trials. In the phase 1 single ascending dose study, TS‐121 capsule (active ingredient: THY1773) showed favorable PKs for THY1773 as expected, and in the separately conducted phase 1 RO study using positron emission tomography, the observed pituitary V1B RO was comparable to our prediction. Retrospective analysis of the prediction accuracy suggested that the prediction methods considering plasma protein binding, and avoiding having to apply unknown scaling factors obtained in animals to humans, would lead to better prediction. Selecting mechanism‐based methods with reasonable assumptions would be critical for the successful prediction of a clinically effective dose in the preclinical stage of drug development. Abstract : We evaluated preclinical pharmacokinetics of THY1773, a novel arginine vasopressin 1B (V1B ) receptor antagonist, and predicted its clinically effective dose for major depressive disorder. Retrospective analysis of prediction accuracy demonstrated that selecting mechanism based methods with reasonable assumptions would be critical for the successful prediction of a clinically effective dose in the preclinical stage of drug development.